Age dependent response to T4 overtreatment and recovery on systemic and organ level. (August 2021) - Kerp, Helena; Renko, Kostja; Hönes, Georg Sebastian; Brix, Klaudia; Köhrle, Josef; Moeller, Lars Christian; Fuehrer, Dagmar
Abstract : Thyroid hormone (TH) metabolism and cellular TH action are influenced by ageing. To investigate response to thyroxine (T4) overtreatment, a kinetic study was conducted in young and aged mice with chronic hyperthyroidism and hormone withdrawal. Five and 22 months old male mice were treated with T4 or PBS over 5 weeks, followed by observation for up to 12 days. Serial analysis was performed for thyroid function parameters, transcript levels of TH target genes, deiodinase type 1 (DIO1) activity as well as serum lipids at 12, 24, 72, 144, 216 and 288h after cessation of T4 administration. Higher FT3 concentrations and higher renal DIO1 activities were noted in aged mice 12h after T4 withdrawal and marked thyroid stimulating hormone elevation was found in aged mice after 12 days compared to respective controls. A biphasic expression pattern occurred for TH target genes in all organs and a hypothyroid organ state was observed at the end of study, despite normalization of TH serum concentrations after 72h. In line with this, mirror image kinetics were detected for serum cholesterol and triglycerides in aged and young mice. Recovery from TH overtreatment in mice involves short and medium-term adaption of TH metabolism on systemic and organ level. Increased renal DIO1 activity may contribute to higher T3 concentrations and prolonged thyrotoxicosis followed by hypothyroidism in an aged mouse organism. Translation of these findings in the clinical setting seems warranted and may lead to a better management of hyperthyroidism and prevention of T4 overtreatment in aged patients.